Predicting the stability of surface phases of molybdenum selenides - Roma, Guido; Ghorbani, Elaheh; Mirhosseini, Hossein; Kiss, Janos; Kühne, Thomas D.; Felser, Claudia (Applied Physics Letters, 2014)
The selenization of molybdenum might become an important step in the production of nanostructures based on the layered compound MoSe2. It is already technologically relevant for the production of thin film chalcopyrite solar cells. However, the control of the process is still very poor, due to the lack of basic knowledge of the surface thermodynamics of the system. Here, we present a theoretical study on the stability of surface adlayers of Se on the Mo(110) surface, predicting surface patterns and their stability range in terms of temperature and selenium partial pressure. Our results, based on density functional theory, show that the attainable Se coverages range from 1/4 to 3/4 of a monolayer for systems in equilibrium with a gas formed of Se molecules. We provide simulated scanning tunneling microscopy images to help the experimental characterization of adsorbed surface patterns.
CRIS-Team Scopus Importer:2023-03-20